The Effect of Red Guava (Psidium guajava l.) Juice on Hemoglobin Levels During Menstruation in Adolescent Girls - Mayasari Putri Ardela; Siti Aminah; Rahma Kusuma Dewi; Raffiky Pinandia Sustamy; Lindha Sri Kusumawati (Journal of Global Research in Public Health, 2023)
Adolescent girls will lose blood which can cause a decrease in hemoglobin levels during menstruation. The function of iron is needed by the body to produce blood. Consumption of foods containing vitamin C plays a role in accelerating the absorption of iron so that it can increase hemoglobin levels during menstruation. Red guava (Psidium guajava l.) has a high vitamin C content of 87 mg/100 grams. This study aims to determine the effect of giving red guava juice on hemoglobin levels during menstruation in adolescent girls at Lirboyo Al-Mahrusiyyah Islamic Boarding School's female dormitory, Kediri, East Java. This research is a true experiment with a randomized pretest-posttest control group design with a sampling technique using simple random sampling. The samples were divided into 4 groups, namely 1 control group (no treatment), and 3 treatment groups with 200 mL/person/day of red guava juice, 250 mL/person/day), and 300 mL/person/day of guava juice. given for 5 days of menstruation. Hemoglobin levels were measured using the Ouik-Check Hemoglobin testing system. The results of the study stated that there was an effect of red guava juice on hemoglobin levels during menstruation (p=0.000). The results of the Tukey HSD test proved that there were differences in hemoglobin levels between groups, namely for the control group with P1 (p=0.004), the control group with P2 (p=0.000), the control group with P3 (p=0.000), P1 and P2 (p = 0.000), and P1 with P3 (p = 0.000). So it can be concluded that giving red guava juice can affect hemoglobin levels during menstruation in adolescent girls.